Plasma acceleration grid surface high-carbon sputtering protection permeation layer and preparation method thereof
By preparing an ultra-thick high-carbon sputtering protective seepage layer on the surface of the molybdenum accelerated gate, the sputtering corrosion and processing and maintenance problems are solved, and efficient sputtering protection and life extension are achieved, while maintaining the conductive and thermal conductivity.
Patent Information
- Application Number
- CN202411567315.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
Existing acceleration gate materials are susceptible to high-energy ion bombardment during service, resulting in sputtering corrosion, resulting in structural corrosion and fatigue damage, and are difficult to process and maintain.
Using the preparation method of a high-carbon sputtering protective seepage layer on the plasma accelerated gate surface, ultra-thick and high-carbon are formed on the surface of the molybdenum gate through nano-treatment treatment, cleaning and photosynthesis pretreatment, carburizing medium coating and high-temperature reaction diffusion technology. Compound protective seepage layer.
It realizes high carbon sputtering protection with adjustable surface thickness of the molybdenum gate, reduces the ion sputtering corrosion rate, significantly improves the service life of the gate, and maintains the conductive thermal performance and processing and maintenance convenience.
Smart Images

Figure CN119433415A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material surface modification, and particularly relates to a method for preparing a high-carbon sputtering protective diffusion layer on the surface of a plasma acceleration grid, and also relates to the high-carbon sputtering protective diffusion layer on the surface of the plasma acceleration grid. Background Art
[0002] The porous accelerating grid is a core component used in semiconductor processing equipment, aerospace ion thrusters, and other application fields to achieve high-precision etching or high-specific impulse propulsion by manipulating low-temperature plasma. It mainly plays the role of accelerating and rectifying the ion jet. A porous mesh structure is usually made of a molybdenum sheet with a thickness of several mm and used as a high-voltage negative electrode. With the help of the high-voltage electric field potential difference, it attracts Ar in the discharge plasma through Coulomb acceleration. + 、Xe + Ions fly toward the gate, which is then guided and rectified using the pore structure to eject a high-energy ion jet in a specific direction and beam intensity. During service, the gate's pore structure connection area and pore walls have a certain probability of being repeatedly bombarded by high-energy ions. A considerable proportion of the energy levels of the bombarding ions are within the range that can trigger rapid sputtering of the gate material. This not only causes the gate material to repeatedly undergo temperature changes and thermal cycles, but also forms a continuous ion etching effect. Therefore, the gate is mainly damaged by sputtering etching superimposed on thermal stress, resulting in structural corrosion or local fatigue damage during service. The gate is made of refractory metal materials such as Mo, mainly because of its ideal electrical and thermal conductivity, mechanical properties, and ease of processing, maintenance, and replacement. However, the lack of anti-sputtering performance has become a major constraint to further improving its service reliability and service life.
[0003] In recent years, through in-depth research on sputtering mechanisms and the continuous accumulation of databases on material sputtering properties, researchers have discovered that the two most important sputtering parameters of a material, the sputtering threshold and sputtering yield, are both related to the atomic number of the material's components. Solid-phase materials formed by elements with smaller atomic numbers have higher sputtering thresholds and lower sputtering yields under ion bombardment at the same energy level. Compared to metals, carbon has a sputtering threshold that is several times higher, or even orders of magnitude higher, and a sputtering yield under normal gate operating conditions that is far lower than that of refractory metals such as molybdenum. Carbon materials also possess excellent electrical and thermal conductivity, high-temperature stability in oxygen-free environments, and superior mechanical properties. As accelerating gate materials or protective layer materials in high vacuum environments, they can potentially achieve extremely low sputtering corrosion rates. The use of various carbon materials to prepare gates or their protective layer materials has become a research hotspot. For example, Haag et al. (Haag TW, Soulas G C. Performance of 8cm Pyrolytic-Graphite Ion Thrruster Optics [C], 38th Joint Propulsion Conference, AIAA-2002-4335, Indianapolis, IN, 2002) developed a 30cm spherical double-grid pyrolytic graphite (PG) grid for the NSTAR thruster. They found that its sputtering erosion rate was significantly reduced compared to molybdenum grids, and its service life was increased by 7-9 times. However, due to the inherent brittleness of PG material, the processing and assembly of this PG grid requires stringent requirements, making it prone to abnormal failures such as substrate cracking during processing and assembly.
[0004] A Chinese patent (application number: 202111051206.3, publication number: CN113773102A, publication date: 2021-09-08) discloses a flange-integrated carbon / carbon screen grid structure for space ion thrusters and its preparation method, using asphalt-based carbon fiber and phenolic resin + mesophase asphalt to prepare a C / C composite grid. Compared with PG materials, the C / C composite material used in this patent has similar sputtering resistance and low thermal expansion coefficient, and shows a lower tendency to crack during processing, molding, assembly and maintenance. However, the C / C composite material is prone to local breakage and shedding of C fibers during grid processing and hole making. Therefore, it faces the problem of hole structure processing where dimensional accuracy is difficult to improve and indicators such as roughness and smoothness are not ideal.
[0005] Kuznetsov et al. (VG Kuznetsov and DK Kostrin 2021J.Phys.:Conf.Ser.1954012026) successfully prepared a pyrolytic carbon coating on the surface of a molybdenum gate by the PECVD method. On the basis of effectively reducing the cost of preparing a full-carbon material gate, they achieved a certain effect of improving the protection life. The main problem is that due to the composition / structure mutation at the interface between the base metal and the carbon coating, the coating is limited to a limited deposition thickness (<10μm) due to the accumulation of high-level mismatch stress. This makes its protection effect close to that of a pure carbon material gate before the coating is etched away, but it is limited by the thickness of the coating and cannot achieve long-life protection.
[0006] The above results show that using all-carbon materials such as PG to prepare the accelerating gate can achieve the most ideal sputtering protection effect and significantly extend the service life of the gate. However, the processing and maintenance difficulty of the gate is much higher than that of the traditional molybdenum gate and is difficult to overcome. The carbon material protective layer prepared on the surface of the molybdenum gate by vapor deposition avoids the gate processing difficulties and replacement and maintenance risks. If the limitation of insufficient thickness can be overcome, it is expected to achieve an ideal protection effect similar to that of the all-carbon gate. Comprehensive literature research shows that the thickness limitation problem is relatively common when using vapor deposition technology to prepare carbon coatings on the surface of metal materials. For example, when depositing amorphous carbon coatings using PVD methods such as magnetron sputtering, it can generally only achieve an effective bonding thickness of less than 5μm. CVD methods such as PECVD have improved but can only achieve an effective bonding thickness of less than 10μm. This requires the solution of forming a carbon-rich protective layer on the surface of the molybdenum gate to seek new technical methods to overcome the limitation of insufficient thickness.
[0007] The research of RNRizakhanova et al. (Rizakhanov RN, Barmin AA, Ivanov AV, et al.. Inorganic Materials: Applied Research, 2015, 6(2): 156-161.) provides a new idea for using compound materials rich in highly sputtering-resistant C, B, and N components to achieve gate protection with the help of selective sputtering mechanism: their research used h-BN powder to prepare an h-BN material gate by hot pressing and sintering at 2000℃ for 0.5h. The selective sputtering behavior of the gate during service formed an enrichment of the sputtering-resistant component B on the material surface, which effectively improved the sputtering resistance of the entire gate component. Although the conductivity of this BN material gate is not ideal, it reveals that the use of compounds or multi-composite materials to form a molybdenum gate protection layer can also use the selective sputtering mechanism to achieve relative enrichment of sputtering protection components such as low atomic numbers B and C on the surface of the gate material and further realize the sputtering protection effect. On this basis, using a high-temperature reaction diffusion process similar to the carburizing of steel materials, it is possible to directly form an ultra-thick high-carbon compound / metal ceramic protective diffusion layer on the surface of the molybdenum gate with more ideal gradient structure / composition characteristics and bonding strength, and a thickness far exceeding that of the vapor-deposited carbon coating, thereby better solving the problems of sputtering protection layer preparation of the acceleration gate and its processing and maintenance. Summary of the Invention
[0008] The purpose of the present invention is to provide a method for preparing a high-carbon sputtering protection diffusion layer on the surface of a plasma acceleration gate, which solves the problems of difficult processing and preparation and poor service performance of existing gate material sputtering protection methods.
[0009] Another object of the present invention is to provide a high carbon sputtering protection layer on the surface of the plasma acceleration grid.
[0010] The technical solution adopted by the present invention is: 1. A method for preparing a high-carbon sputtering protective diffusion layer on the surface of a plasma acceleration gate, characterized by being implemented in accordance with the following steps:
[0011] Step 1, the surface of the molybdenum gate is nano-processed;
[0012] Step 2, cleaning and finishing the molybdenum gate material obtained in step 1;
[0013] Step 3, coating and packaging the molybdenum gate material obtained in step 2 with a carburizing medium;
[0014] Step 4: Select a specific temperature for reactive diffusion carburizing to form a high-carbon sputtering protective carburized layer on the surface.
[0015] The present invention is also characterized in that:
[0016] In step 1, specifically:
[0017] The surface of the molybdenum gate material was subjected to ultrasonic impact nano-treatment, using a single needle processing gun head with an impact head diameter of 3 mm, an impact frequency of 20 kHz, an impact amplitude of 50 μm, and a travel speed of 2 mm / s. The surface was repeatedly impacted until the coverage rate was 300%.
[0018] In step 2, specifically:
[0019] The molybdenum gate material obtained in step 1 is pickled in dilute hydrochloric acid or dilute sulfuric acid; then it is polished step by step with metallographic sandpaper to 2000-3000 mesh, and then polished until the surface roughness Ra reaches 0.05. Finally, it is ultrasonically cleaned with anhydrous ethanol and placed in a drying oven for drying after cleaning.
[0020] In step 3, specifically:
[0021] The ultrafine carbon black powder and carbonate are evenly mixed and then placed in a corundum crucible. The molybdenum gate substrate obtained in step 2 is coated in the mixed powder of carbon black and carbonate. The crucible is covered with a lid, and the connection between the crucible lid and the crucible is coated with high-temperature refractory glue.
[0022] The average particle size of the ultrafine micron-grade carbon black powder is 5 μm, and the carbonate is any one of anhydrous sodium carbonate, barium carbonate, and calcium carbonate; the mass ratio of the carbon black powder to the carbonate is 9:1.
[0023] In step 4, specifically:
[0024] The crucible sealed with high-temperature refractory glue in step 3 is placed in a vacuum furnace, and the furnace is evacuated by an oil-sealed mechanical vacuum pump until the vacuum gauge display value stabilizes at -0.1 MPa, and then argon is introduced. The vacuuming and argon introduction are repeated 3 times, and then argon is continuously introduced for atmosphere protection and high-temperature dissolution and diffusion reactions are started. The high-temperature dissolution and diffusion reaction process is specifically divided into three stages: a preheating period, a high-temperature enrichment period, and a diffusion and dissolution period. After repeating the high-temperature dissolution and diffusion three times, the furnace is cooled to room temperature to complete carbon impregnation and diffusion; the metal substrate is then ultrasonically cleaned and dried to form a high-carbon sputtering protective impregnation layer on the metal base surface.
[0025] The high temperature dissolution and diffusion reaction is specifically as follows:
[0026] A) Preheating temperature rise period: from room temperature to preheating temperature T at a rate of 8℃ / min p Keep warm for 10-40min; T p 900-950℃;
[0027] B) High temperature enrichment period: the temperature was increased from T p Heating to enrichment temperature Th After 120 minutes of heat preservation, the surface enrichment of C and a certain degree of high-temperature reaction diffusion are completed. h 1200-1500℃;
[0028] C) Diffusion dissolution period: The diffusion dissolution period was 8℃ / min from different T h Cool down 50℃ to the diffusion and dissolution temperature T d And keep warm for 30 minutes.
[0029] Another technical solution adopted by the present invention is to prepare a protective diffusion layer by a method for preparing a high-carbon sputtering protective diffusion layer on the surface of a plasma accelerated gate.
[0030] The beneficial effects of the present invention are:
[0031] The present invention discloses a method for preparing a high-carbon sputtering protective layer on the surface of a plasma-accelerated gate. This method involves performing surface nano-nano-high-frequency micro-deformation processing on a finished molybdenum gate to achieve surface metallization cleaning and diffusion-enhanced treatment. This is then combined with a high-temperature diffusion reaction process on the surface layer in an atmosphere-protected solid carbon-rich medium to produce a high-carbon compound protective layer of sufficient thickness (200 μm, typically >100 μm) metallurgically bonded to the molybdenum matrix. This method not only inherits the ideal processing and maintenance characteristics of the molybdenum gate, but also meets the dimensional accuracy requirements of the gate pore structure and maintains its excellent electrical and thermal conductivity. The present invention utilizes the Mo2C phase transitional reactive diffusion utilization technology proposed and established by the present invention. By selecting the diffusion temperature within the two-phase region where the Mo2C phase and other high-carbon phases (MoC, GLC, etc.) coexist, a carbon concentration gradient within the Mo2C phase is continuously maintained by utilizing the carbon solubility range of the medium- and low-carbon Mo2C phase itself, overcoming the carbon diffusion shielding effect that often occurs after the high-carbon phase is continuously generated due to the absence of a carbon concentration gradient within the phase. On this basis, combined with the alternating cycle enrichment-dissolution reaction diffusion process design, the high-concentration carbon atoms enriched in the surface layer can be promoted to continue to diffuse deeply, and at the same time, an ultra-thick diffusion layer depth of more than 100μm and a carbon concentration gradient distribution from the surface to the inside of the diffusion layer can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Graph showing the carbon concentration versus depth of the high carbon sputtering protection layer in Examples 2 and 3 of the present invention;
[0033] Figure 2 This is a backscattered electron image of the high-carbon sputtering protective layer on the surface of the molybdenum gate prepared in Example 3 of the present invention;
[0034] Figure 3 This is the energy spectrum of the high-carbon sputtering protective layer on the surface of the molybdenum gate prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0035] The present invention will be described in detail below with reference to specific embodiments and the accompanying drawings.
[0036] The method for preparing a high-carbon sputtering protective diffusion layer on the surface of a plasma acceleration gate of the present invention is specifically implemented according to the following steps:
[0037] Step 1: nano-processing the surface of the molybdenum gate; specifically:
[0038] The surface of the molybdenum gate material was subjected to ultrasonic impact nano-treatment using a single-needle machining gun tip with an impact head diameter of 3 mm, an impact frequency of 20 kHz, an impact amplitude of 50 μm, and a travel speed of 2 mm / s. The surface was repeatedly impacted until the coverage rate reached 300%.
[0039] Step 2, cleaning and finishing the molybdenum gate material obtained in step 1;
[0040] Specifically, the molybdenum gate material obtained in step 1 is pickled in dilute hydrochloric acid or dilute sulfuric acid to remove the surface oxide film. It is then sanded to 2000-3000 grit using metallographic sandpaper, and then polished to a surface roughness Ra of 0.05. Finally, it is ultrasonically cleaned with anhydrous ethanol at a frequency of 40 kHz for 15 minutes. After cleaning, it is dried in a drying oven at 60°C for 30 minutes.
[0041] Step 3, coating and packaging the molybdenum gate material obtained in step 2 with a carburizing medium;
[0042] The ultrafine carbon black powder and carbonate are uniformly mixed and then placed in a corundum crucible. The molybdenum gate substrate obtained in step 2 is coated in the mixed powder of carbon black and carbonate. The crucible is covered with a lid, and the connection between the crucible lid and the crucible is coated with a high-temperature refractory glue;
[0043] The average particle size of the ultrafine micron-grade carbon black powder is 5 μm, and the carbonate is any one of anhydrous sodium carbonate, barium carbonate, and calcium carbonate;
[0044] The mass ratio of carbon black powder to carbonate is 9:1;
[0045] Among them, the components of high-temperature refractory glue are silicate, yttrium, and lanthanum oxide, which are completely coated on the connection between the crucible and the crucible cover to avoid the overflow of carbon-rich atmosphere during the high-temperature diffusion stage while effectively preventing the oxidation of metal materials.
[0046] Step 4: Select a specific temperature for reactive diffusion carburizing to form a high-carbon sputtering protective carburized layer on the surface;
[0047] The crucible sealed with high-temperature refractory glue in step 3 is placed in a vacuum furnace, and the furnace is evacuated using an oil-sealed mechanical vacuum pump until the vacuum gauge reading is close to -0.1 MPa and argon is introduced after stabilization. The vacuuming and argon introduction are repeated three times to ensure that the furnace cavity is a pure protective atmosphere. Argon is then continuously introduced for atmosphere protection and the high-temperature dissolution and diffusion reaction is started. At this time, the vacuum gauge reading is close to 0;
[0048] The high-temperature dissolution and diffusion reaction process is divided into three stages:
[0049] A) Preheating temperature rise period: from room temperature to preheating temperature T at a rate of 8℃ / min p Keep warm for 10-40min; T p Depending on the gate material and size characteristics, the temperature can be selected within the range of 900-950°C, preferably 930°C;
[0050] B) High temperature enrichment period: the temperature was increased from T p Heating to enrichment temperature T h After 120 minutes of heat preservation, the surface enrichment of C and a certain degree of high-temperature reaction diffusion are completed. h The temperature should be selected within the range of 1200-1500℃ according to the different requirements of the penetration layer depth and reaction diffusion degree;
[0051] C) Diffusion dissolution period: The diffusion dissolution period was 8℃ / min from different T h Cool down 50℃ to the diffusion and dissolution temperature T d The temperature is kept for 30 minutes to enhance the further diffusion and dissolution of the high carbon compound phase generated by the reaction diffusion, so as to ease the carbon concentration distribution gradient in the carburized layer;
[0052] After repeating high-temperature dissolution and diffusion three times, the furnace is cooled to room temperature to complete carbon impregnation and diffusion; the metal substrate is then ultrasonically cleaned and placed in a drying oven to dry, forming a high-carbon sputtering protective impregnation layer on the metal base surface;
[0053] Use anhydrous ethanol or acetone for cleaning, the ultrasonic frequency is 40KHz, and the cleaning time is 15 minutes;
[0054] The molybdenum gate material sealed in the crucible needs to be preheated in stage A and then alternately undergo high-temperature enrichment in stage B and diffusion dissolution in stage C for three cycles before the reaction diffusion treatment is completed and a high carbon protective layer is formed on the surface of the molybdenum gate. h 、T dDepending on the treatment temperature, the corresponding protective carburized layer phase composition characteristics can be classified into different categories such as α-Mo+Mo2C, Mo2C+MoC, Mo2C and Mo2C+C (GLC), and different carburized layer thicknesses, maximum carbon content in the surface layer and carbon concentration distribution in the carburized layer can be achieved.
[0055] After a high concentration difference is formed during the high-temperature enrichment phase, a concentration gradient is used to fully diffuse the activated carbon. This prevents excessive cracking reactions at high temperatures, which can lead to surface carbon oversaturation and the accumulation of carbon black, which would otherwise form a barrier layer that hinders the metal matrix's continued adsorption of the activated carbon. After the dissolution and diffusion phases are cycled, the carbon is cooled to room temperature to complete carbon impregnation and reactive diffusion.
[0056] The present invention selects to subject the finished molybdenum grid to surface nano-crystallization catalytic infiltration pretreatment by ultrasonic impact processing, and utilizes the large number of newly formed grain boundaries and high-density dislocations in the processed nanocrystalline structure generated after the surface metal is subjected to high-frequency micro-deformation to provide a short-circuit diffusion path for the adsorption and infiltration of C atoms and strengthen the diffusion kinetic conditions of the carburizing reaction; through the steps of pickling, polishing and ultrasonic cleaning, the adsorbed impurities and oxidation products of the impact-processed surface are removed, so as to achieve the purpose of making the nano-crystallized surface clean and metallized so as to fully contact the carburizing medium; ultra-fine carbon black powder is mixed with a certain proportion of catalytic carbonate to form a solid carbon source, and its fluidity and strong adsorption effect are used to ensure that it can penetrate the ultra-thin multi-layer grid. The surface metal is fully contacted and effectively coated in the complex porous structure, which is conducive to the adsorption and penetration of carbon atoms released by the carbon source at high temperature; by selecting the high-temperature carbon enrichment and diffusion dissolution temperature in the reaction diffusion stage in the specific carbide two-phase coexistence temperature range, the carbon concentration gradient of the diffusion layer is continuously maintained after the continuous formation of the carbide phase; combined with multiple cycles of high-temperature enrichment-dissolution-diffusion alternating cycles to promote the continuous diffusion and penetration of high-concentration carbon atoms in the surface layer, while continuously increasing the carbon content of the surface layer, ensuring the continuous growth and thickening of the high-carbon compound diffusion layer, so as to achieve the purpose of preparing a high-carbon compound sputtering-resistant protective diffusion layer with both ultra-thick scale and gradient distribution of carbon concentration characteristics.
[0057] The present invention provides a method for preparing a high-carbon sputtering protection layer on the surface of a plasma acceleration grid. This method addresses the problem of molybdenum grids, which have ideal electrical, thermal, and mechanical properties and are easy to process, maintain, and replace, but lack sputtering resistance. By directly performing a carbon-enriched surface treatment on the finished molybdenum grid, the finished molybdenum grid achieves sputtering resistance approaching that of a full-carbon material grid while maintaining essentially unchanged dimensional accuracy and electrical and thermal conductivity. This provides a practical engineering solution for maintaining the use of low-cost molybdenum grids while effectively improving their sputtering resistance and long-life service reliability. Following the method of the present invention, the molybdenum grid material undergoes surface nano-crystallization and clean metallization pretreatments, followed by cyclic high-temperature reaction-diffusion treatment at a specific temperature in a carbon-rich medium within an atmosphere-protected furnace. This yields an ultra-thick, high-carbon sputtering protection layer with a thickness adjustable within a range of 5-167 μm, a surface carbon content of 51-73 at%, and reliable metallurgical bonding with the metal molybdenum substrate while maintaining a gradient carbon concentration distribution. The selective sputtering mechanism of the high-carbon compound layer further enables spontaneous carbon enrichment on the surface of the molybdenum gate during service. By leveraging the sputtering resistance of the carbon component, the ion sputtering corrosion rate of the molybdenum gate under normal operating conditions can be reduced by more than 6 times. The key to the present invention lies in the uniquely proposed and implemented Mo2C phase transition reaction diffusion technology. This method ensures that the layer composition always contains a certain proportion of Mo2C by selecting the reaction diffusion temperature within the coexistence region of the Mo2C phase and other higher carbon compound phases, and continuously generates other high-carbon phases (MoC, GLC). On the one hand, the carbon concentration gradient formed within the carbon solubility range of the Mo2C phase allows carbon atoms to diffuse deeply and continuously, effectively overcoming the diffusion barrier effect of other high-carbon phases with fixed carbon content, and promoting the continuous increase of the layer thickness. On the other hand, the enrichment-dissolution reaction diffusion process, through multiple cycles of alternating cycles, continuously increases the relative proportion of the high-carbon phase in the surface region, ultimately achieving a compound layer generated by the reaction diffusion process with high surface carbonization, gradient composition, and ultra-thickness.
[0058] Example 1
[0059] The molybdenum material is subjected to ultrasonic impact at a frequency of 20kHz, an amplitude of 50μm, and a travel speed of 2mm / s, and the surface is repeatedly impacted until the surface coverage reaches 300%. The molybdenum material composition by mass is Fe 0.01%, Mg 0.002%, Si 0.01%, C 0.01%, Ni 0.005%, O 0.008%, and the remainder is Mo.
[0060] The resulting molybdenum gate material was pickled in dilute hydrochloric acid to remove the surface oxide film. It was then sanded to 3000 grit using metallographic sandpaper and polished to a surface roughness Ra of 0.05. Finally, it was ultrasonically cleaned with anhydrous ethanol at a frequency of 40 kHz for 15 minutes. After cleaning, it was dried in a drying oven at 60°C for 30 minutes.
[0061] Carbon black powder with an average particle size of 5 μm and sodium carbonate are uniformly mixed in a mass ratio of 9:1, and then placed in a corundum crucible. The gate substrate obtained after pre-cleaning is coated in the mixed powder of carbon black and carbonate. The crucible is covered with a lid, and the connection between the crucible lid and the crucible is coated with high-temperature refractory glue;
[0062] The crucible sealed with high-temperature refractory glue was placed in a vacuum furnace. An oil-sealed mechanical vacuum pump was used to evacuate the furnace until the vacuum gauge reading was close to -0.1 MPa and stabilized, and argon was introduced. The vacuuming and argon introduction were repeated three times to ensure a pure protective atmosphere in the furnace cavity. Argon was then continuously introduced for atmosphere protection and a high-temperature diffusion reaction was started. At this time, the vacuum gauge reading was near 0, the argon purity was 99.99%, and the flow rate was 2 ml / min.
[0063] The preheating phase began at room temperature and pressure, with a heating rate of 8°C / min. The sample was heated to 930°C and held for 30 minutes. After the preheating phase, the temperature was increased to 1050°C at 6°C / min and held for 120 minutes to perform high-temperature carbon enrichment. After the high-temperature enrichment phase, the sample was cooled to 1000°C at 8°C / min and held for 30 minutes to initiate the diffusion dissolution process. The high-temperature enrichment and diffusion dissolution processes were repeated three times to complete the reaction diffusion process. After the sample cooled to room temperature, it was removed for ultrasonic cleaning and placed in a drying oven for drying. Ultrasonic cleaning was performed using anhydrous ethanol at an ultrasonic frequency of 40 kHz for 15 minutes. After cleaning, the sample was placed in a drying oven and dried at 60°C for 30 minutes before being removed. Scanning electron microscopy and XRD analysis revealed that the protective layer on the surface of the molybdenum gate had a phase composition of α-Mo + Mo2C, a surface carbon content of 51 At%, and a thickness of 5 μm.
[0064] Example 2
[0065] The molybdenum material is subjected to ultrasonic impact at a frequency of 20kHz, an amplitude of 50μm, and a travel speed of 2mm / s, and the surface is repeatedly impacted until the surface coverage reaches 300%. The molybdenum material composition by mass is Fe 0.01%, Mg 0.002%, Si 0.01%, C 0.01%, Ni 0.005%, O 0.008%, and the remainder is Mo.
[0066] The resulting molybdenum gate material was pickled in dilute hydrochloric acid to remove the surface oxide film. It was then sanded to 3000 grit using metallographic sandpaper and polished to a surface roughness Ra of 0.05. Finally, it was ultrasonically cleaned with anhydrous ethanol at a frequency of 40 kHz for 15 minutes. After cleaning, it was dried in a drying oven at 60°C for 30 minutes.
[0067] Carbon black powder with an average particle size of 5 μm and sodium carbonate are uniformly mixed in a mass ratio of 9:1, and then placed in a corundum crucible. The gate substrate obtained after pre-cleaning is coated in the mixed powder of carbon black and carbonate. The crucible is covered with a lid, and the connection between the crucible lid and the crucible is coated with high-temperature refractory glue;
[0068] The crucible sealed with high-temperature refractory glue was placed in a vacuum furnace. An oil-sealed mechanical vacuum pump was used to evacuate the furnace until the vacuum gauge reading was close to -0.1 MPa and stabilized, and argon was introduced. The vacuuming and argon introduction were repeated three times to ensure a pure protective atmosphere in the furnace cavity. Argon was then continuously introduced for atmosphere protection and a high-temperature diffusion reaction was started. At this time, the vacuum gauge reading was near 0, the argon purity was 99.99%, and the flow rate was 2 ml / min.
[0069] The preheating phase began at room temperature and pressure, with a heating rate of 8°C / min. The sample was heated to 930°C and held for 30 minutes. After the preheating phase, the sample was heated to 1200°C at a rate of 6°C / min and held for 120 minutes to perform high-temperature carbon enrichment. After the high-temperature enrichment phase, the sample was cooled to 1150°C at a rate of 8°C / min and held for 30 minutes to initiate the diffusion dissolution process. The high-temperature enrichment and diffusion dissolution processes were repeated three times to complete the reaction-diffusion process. After the sample cooled to room temperature, it was removed for ultrasonic cleaning and dried in a drying oven. Ultrasonic cleaning was performed using anhydrous ethanol at a frequency of 40 kHz for 15 minutes. After cleaning, the sample was placed in a drying oven and dried at 60°C for 30 minutes before removal. Scanning electron microscopy and XRD analysis revealed a protective layer with a phase composition of Mo2C+MoC on the surface of the molybdenum gate, a surface carbon content of 56.49 At%, and a thickness of 29 μm.
[0070] Example 3
[0071] The molybdenum material was subjected to ultrasonic impact at a frequency of 20 kHz, an amplitude of 50 μm, and a travel speed of 2 mm / s, and the surface was repeatedly impacted until the coverage rate reached 300%. The molybdenum material composition by mass is Fe 0.01%, Mg 0.002%, Si 0.01%, C 0.01%, Ni 0.005%, O 0.008%, and the remainder is Mo.
[0072] The resulting molybdenum gate material was pickled in dilute hydrochloric acid to remove the surface oxide film. It was then sanded to 3000 grit using metallographic sandpaper and polished to a surface roughness Ra of 0.05. Finally, it was ultrasonically cleaned with anhydrous ethanol at a frequency of 40 kHz for 15 minutes. After cleaning, it was dried in a drying oven at 60°C for 30 minutes.
[0073] Carbon black powder with an average particle size of 5 μm and sodium carbonate are uniformly mixed in a mass ratio of 9:1, and then placed in a corundum crucible. The gate substrate obtained after pre-cleaning is coated in the mixed powder of carbon black and carbonate. The crucible is covered with a lid, and the connection between the crucible lid and the crucible is coated with high-temperature refractory glue;
[0074] The crucible sealed with high-temperature refractory glue was placed in a vacuum furnace. An oil-sealed mechanical vacuum pump was used to evacuate the furnace until the vacuum gauge reading was close to -0.1 MPa and stabilized, and argon was introduced. The vacuuming and argon introduction were repeated three times to ensure a pure protective atmosphere in the furnace cavity. Argon was then continuously introduced for atmosphere protection and a high-temperature diffusion reaction was started. At this time, the vacuum gauge reading was near 0, the argon purity was 99.99%, and the flow rate was 2 ml / min.
[0075] The preheating phase began at room temperature and pressure, with a heating rate of 8°C / min. The sample was heated to 930°C and held for 30 minutes. After the preheating phase, the temperature was increased to 1350°C at 6°C / min and held for 120 minutes to carry out high-temperature carbon enrichment. After the high-temperature enrichment phase, the sample was cooled to 1300°C at 8°C / min and held for 30 minutes to initiate the diffusion dissolution process. The high-temperature enrichment and diffusion dissolution processes were repeated three times to complete the reaction diffusion process. After the sample cooled to room temperature, it was removed for ultrasonic cleaning and placed in a drying oven for drying. Ultrasonic cleaning was performed using anhydrous ethanol at an ultrasonic frequency of 40 kHz for 15 minutes. After cleaning, the sample was placed in a drying oven and dried at 60°C for 30 minutes before being removed. Scanning electron microscopy and XRD analysis revealed that the protective layer on the surface of the molybdenum gate had a phase composition of Mo2C+MoC, a surface carbon content of 60.78 At%, and a thickness of 76 μm.
[0076] Example 4
[0077] Ultrasonic impact on molybdenum material, impact frequency 20kHz, impact amplitude 50 m, with a walking speed of 2 mm / s, and repeatedly impacting the surface until the coverage rate reaches 300%. The molybdenum material composition by mass percentage is Fe 0.01%, Mg 0.002%, Si 0.01%, C 0.01%, Ni 0.005%, O 0.008%, and the rest is Mo.
[0078] The resulting molybdenum gate material was pickled in dilute hydrochloric acid to remove the surface oxide film. It was then sanded to 3000 grit using metallographic sandpaper and polished to a surface roughness Ra of 0.05. Finally, it was ultrasonically cleaned with anhydrous ethanol at a frequency of 40 kHz for 15 minutes. After cleaning, it was dried in a drying oven at 60°C for 30 minutes.
[0079] Carbon black powder with an average particle size of 5 μm and sodium carbonate are uniformly mixed in a mass ratio of 9:1, and then placed in a corundum crucible. The gate substrate obtained after pre-cleaning is coated in the mixed powder of carbon black and carbonate. The crucible is covered with a lid, and the connection between the crucible lid and the crucible is coated with high-temperature refractory glue;
[0080] The crucible sealed with high-temperature refractory glue was placed in a vacuum furnace. An oil-sealed mechanical vacuum pump was used to evacuate the furnace until the vacuum gauge reading was close to -0.1 MPa and stabilized, and argon was introduced. The vacuuming and argon introduction were repeated three times to ensure a pure protective atmosphere in the furnace cavity. Argon was then continuously introduced for atmosphere protection and a high-temperature diffusion reaction was started. At this time, the vacuum gauge reading was near 0, the argon purity was 99.99%, and the flow rate was 2 ml / min.
[0081] The preheating phase began at room temperature and pressure, with a heating rate of 8°C / min. The sample was heated to 930°C and held for 30 minutes. After the preheating phase, the sample was heated to 1500°C at a rate of 6°C / min and held for 120 minutes to perform high-temperature carbon enrichment. After the high-temperature enrichment phase, the sample was cooled to 1450°C at a rate of 8°C / min and held for 30 minutes to initiate the diffusion dissolution process. The high-temperature enrichment and diffusion dissolution processes were repeated three times to complete the reaction-diffusion process. After the sample cooled to room temperature, it was removed for ultrasonic cleaning and dried in a drying oven. Ultrasonic cleaning was performed using anhydrous ethanol at a frequency of 40 kHz for 15 minutes. After cleaning, the sample was placed in a drying oven and dried at 60°C for 30 minutes before removal. Scanning electron microscopy and XRD analysis revealed a protective layer with a phase composition of Mo2C+GLC on the surface of the molybdenum gate, a surface carbon content of 73.45 At%, and a thickness of 167 μm.
[0082] Example 5
[0083] Table 1 shows the protection effect and characteristic parameters of the diffusion layer of the untreated molybdenum gate and the different embodiments obtained after the surface high carbonization treatment of the molybdenum gate material by the method of the present invention under different process conditions. The results show that the method of the present invention can successfully prepare a high carbon diffusion layer with a thickness of 5-167μm on the surface of the molybdenum gate by regulating the high-temperature reaction and diffusion conditions, and obtain different diffusion layer phase compositions (specifically, α-Mo+Mo2C, Mo2C, Mo2C+MoC, Mo2C+GLC and other combinations). After the corresponding treatment, the carbon content of the molybdenum gate surface can reach 51-73at% and the carbon concentration gradient distribution characteristics are maintained in the diffusion layer (see for details). Figure 1 The comparative data of the variation of the composition of the diffusion layer with the distance from the surface in Examples 2 and 3 are given as well as Figure 2 、 3 The SEM image of the cross section of the diffusion layer of Example 4 and the elemental composition of the diffusion layer surface measured by EDS spectrum of Example 4 are given respectively. The measured ion sputtering corrosion rate of the untreated molybdenum gate under simulated service conditions is about 3.42nm / s, while the treated molybdenum gate can effectively reduce the ion sputtering corrosion rate to 0.63-0.51nm / s by virtue of the high carbon protective diffusion layer generated by its surface reaction diffusion combined with the selective sputtering mechanism, achieving more than 6 times the anti-sputtering performance and theoretical service life improvement effect. At the same time, Table 1 and Figure 3 The test results also show that after treatment with the method of the present invention, due to the metal-ceramic composition characteristics of the protective diffusion layer and its good metallurgical interface bonding with the base metal, as well as the maximum thickness of no more than 200 μm, the surface conductivity of the molybdenum gate material after treatment in different embodiments only slightly decreased from the 31.7% IACS level of the untreated molybdenum gate to the range of 31.0-31.4% IACS, with a change rate of less than 2%. This confirms that the ability of the treated molybdenum gate to establish a high-voltage electric field to guide the ion beam is almost unaffected, and can meet the conductivity and bonding strength requirements of the gate service.
[0084] Table 1 Comparison of protection effects and characteristic parameters of the embodiment and untreated molybdenum gate materials
[0085]
[0086] Example 6
[0087] The results of the embodiments of the present invention show that the thickness of the surface diffusion layer of the molybdenum gate obtained by the method of the present invention can be controlled in the range of 5-167μm, the corresponding surface carbon content can reach 51-73at% and the gradient carbon concentration distribution characteristics are maintained in the diffusion layer. This allows the molybdenum gate material to achieve further surface carbon enrichment through the selective sputtering mechanism of the ultra-thick high-carbon diffusion layer after treatment, and rely on the excellent sputtering resistance of the surface-enriched carbon component itself to reduce the ion sputtering corrosion rate of the untreated molybdenum gate under service conditions from approximately 3.42nm / s to 0.59-0.51nm / s, achieving a theoretical lifespan increase of more than 6 times. This shows that the method of the present invention achieves a sputtering protection effect close to that of a full-carbon material gate, while maintaining the processing accuracy, maintenance and replacement convenience, and excellent thermal and electrical conductivity of the molybdenum gate, providing a practical engineering solution for continuing to use low-cost molybdenum gates and effectively improving their sputtering resistance and long-life service reliability.
Claims
1. A method for preparing a high carbon sputtering protective diffusion layer on the surface of a plasma acceleration grid, characterized in that: Follow the steps below to implement it: Step 1, the surface of the molybdenum gate is nano-processed; Step 2, cleaning and finishing the molybdenum gate material obtained in step 1; Step 3, coating and packaging the molybdenum gate material obtained in step 2 with a carburizing medium; Step 4, selecting a specific temperature for reactive diffusion carburizing, so as to form a high carbon sputtering protective carburized layer on the surface.
2. The method for preparing a high carbon sputtering protective diffusion layer on the surface of a plasma acceleration grid as claimed in claim 1, characterized in that: In the step 1, specifically: The surface of the molybdenum gate material was subjected to ultrasonic impact nano-treatment, using a single-needle processing gun head with an impact head diameter of 3 mm, an impact frequency of 20 kHz, an impact amplitude of 50 μm, and a travel speed of 2 mm / s. The surface was repeatedly impacted until the coverage rate was 300%.
3. The method for preparing a high carbon sputtering protective diffusion layer on the surface of a plasma acceleration grid as claimed in claim 1, characterized in that: In the step 2, specifically: The molybdenum gate material obtained in step 1 is pickled in dilute hydrochloric acid or dilute sulfuric acid; then it is polished step by step with metallographic sandpaper to 2000-3000 mesh, and then polished until the surface roughness Ra reaches 0.05, and finally ultrasonically cleaned with anhydrous ethanol. After cleaning, it is placed in a drying oven for drying.
4. The method for preparing a high carbon sputtering protective layer on the surface of a plasma acceleration grid as claimed in claim 1, characterized in that: In the step 3, specifically: The ultrafine micron-sized carbon black powder is uniformly mixed with carbonate, and then placed in a corundum crucible, the molybdenum gate substrate obtained in step 2 is coated in the mixed powder of carbon black and carbonate, the crucible is covered, and the connection between the crucible cover and the crucible is coated with high-temperature refractory glue.
5. The method for preparing a high carbon sputtering protective diffusion layer on the surface of a plasma acceleration grid as claimed in claim 4, characterized in that: The average particle size of the ultrafine micron-grade carbon black powder is 5 μm, and the carbonate is any one of anhydrous sodium carbonate, barium carbonate, and calcium carbonate; the mass ratio of the carbon black powder to the carbonate is 9:
1.
6. The method for preparing a high carbon sputtering protective diffusion layer on the surface of a plasma acceleration grid as claimed in claim 1, characterized in that: In the step 4, specifically: The crucible sealed by the high-temperature refractory glue coating in step 3 is placed in a vacuum furnace, and the furnace is evacuated by an oil-sealed mechanical vacuum pump until the vacuum gauge display value stabilizes at -0.1MPa, and then argon gas is introduced. The vacuuming and argon introduction are repeated 3 times, and then argon gas is continuously introduced for atmosphere protection and high-temperature dissolution and diffusion reactions are started. The high-temperature dissolution and diffusion reaction process is specifically divided into three stages: a preheating period, a high-temperature enrichment period, and a diffusion and dissolution period. After repeating the high-temperature dissolution and diffusion three times, the furnace is cooled to room temperature to complete carbon infiltration and diffusion; then the metal substrate is ultrasonically cleaned and dried to form a high-carbon sputtering protective infiltration layer on the surface of the metal base.
7. The method for preparing a high carbon sputtering protective diffusion layer on the surface of a plasma acceleration grid as claimed in claim 6, characterized in that: The high temperature dissolution and diffusion reaction is specifically: A) Preheating period: from room temperature to preheating temperature T at a rate of 8°C / min p After heat preservation for 10-40min; T p 900-950℃; B) High temperature enrichment period: at a rate of 6℃ / min from T p Heating to enrichment temperature T h After 120 minutes of heat preservation, the surface enrichment of C and a certain degree of high-temperature reaction diffusion are completed. h 1200-1500℃; C) Diffusion dissolution period: at a rate of 8℃ / min from different T h Cool down 50℃ to diffusion dissolution temperature T d And keep warm for 30 minutes.
8. The protective diffusion layer prepared by the method for preparing a high carbon sputtering protective diffusion layer on the surface of a plasma acceleration gate as described in any one of claims 1 to 7.
Citation Information
Patent Citations
Flange integrated carbon / carbon screen gate structure and preparation method thereof
CN113773102A
An integrated flange carbon / carbon screen gate structure and its fabrication method
CN113773102B